Use of information and communication technologies as a support tool for medical students’ learning - Cervantes-López, Miriam Janet (Universidad Autónoma de Tamaulipas, 2020)
The use of electronic devices as educational tools is very frequent in the global knowledge society, which has been favored by current technological advancement. New alternatives are employed in teaching practice and in educational processes, and institutions dedicated to medical education are no exception. The objective of this work was to establish whether the use of information and communication technologies (ICT) for medical students’ learning at the Autonomous University of Tamaulipas, Southern campus. A descriptive, observational and crosssectional study was carried out. Data was collected through a questionnaire administered to 109 students. Of the total number of participants, 90.83 % had a laptop, 94.50 % had internet access, either via a computer or a mobile phone. The effective time spent daily using ICT for educational activities ranged between two and four hours, and Google Scholar was the most used database for information retrieval. On the other hand, it was found that between 50 % and 75 % of respondents have an understanding and command of the English language. The use of ICT’s is very supportive for students, since it facilitates both, the scientific and medical information retrieval, as well as the development of competencies in the processing and management of information. This simplifies the exchange of updated scientific information to continue with their medical education.